2006
DOI: 10.1175/jcli3918.1
|View full text |Cite
|
Sign up to set email alerts
|

Projection and Analysis of Extreme Wave Climate

Abstract: The nonhomogeneous Poisson process is used to model extreme values of the 40-yr ECMWF Re-Analysis (ERA-40) significant wave height. The parameters of the model are expressed as functions of the seasonal mean sea level pressure anomaly and seasonal squared sea level pressure gradient index. Using projections of the sea level pressure under three different forcing scenarios by the Canadian coupled climate model, projections of the parameters of the nonhomogeneous Poisson process are made, trends in these project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(103 citation statements)
references
References 16 publications
2
99
1
1
Order By: Relevance
“…A number of modelling studies suggest that, in the future, increases in extreme wave height are likely to occur in the mid-latitude oceans (e.g. Wang et al 2004;Caires et al 2006). Woth et al (2006) found that, for the North Sea, a 100-year event could become 10-20 cm higher than today by the 2080s.…”
Section: Expected Change In Storm Surgesmentioning
confidence: 99%
“…A number of modelling studies suggest that, in the future, increases in extreme wave height are likely to occur in the mid-latitude oceans (e.g. Wang et al 2004;Caires et al 2006). Woth et al (2006) found that, for the North Sea, a 100-year event could become 10-20 cm higher than today by the 2080s.…”
Section: Expected Change In Storm Surgesmentioning
confidence: 99%
“…Therefore it is difficult to quantitatively assess the relative contribution between more than two factors at a time. Wang et al (2004), Wang and Swail (2006a) as well as Caires et al (2006) used one climate model (the Canadian CGCM2) for different emission scenarios. Wang and Swail (2006b), however, represented the average of three models for the emission scenarios A2 and B2.…”
Section: Uncertainties Related To Wave Climate Projectionsmentioning
confidence: 99%
“…Both seasonal mean SLP anomalies, P, and anomalies of seasonal mean squared SLP gradients, G, have been shown to be good predictors for predicting seasonal SWH statistics (Wang and Swail 2006a, b;Wang et al 2004;Caires et al 2006). The use of predictor anomalies, instead of predictor values, diminishes the effects of 'model climate biases', i.e.…”
Section: Effect Of Downscalingmentioning
confidence: 99%
See 2 more Smart Citations